The Impact of Augmented Reality in English Learning in Elementary Schools - Rugaiyah; Istiqamah Ardila; Unan Yusmaniar Oktiawati; Nanda Saputra (Jurnal Ilmiah Sekolah Dasar, 2024)
The role of language as the most important means of effective communication is universally recognized. In the context of education, students are expected to recognize the potential for acquiring English with the help of the media. Media is a tool for learning English. The use of media in learning English is minimal. The aim is to find out the results of applying augmented reality as a medium for learning English in elementary schools. The method in this research is mixed methods namely survey, observation, and documentation. The subjects of this study were a teacher and elementary school students in English subject. Data collection techniques, nonverbal in the form of pictures, assisted by recording techniques, with the listening method. Data collection instruments used questionnaires and interview sheets. Multimodal analysis techniques and interview results were collected, reduced, and concluded. The results of the study show that teachers can use learning media based on augmented reality in learning English well. There is an increase in student learning outcomes in English subjects after using augmented reality-based learning media. So, can be concluded that the increased satisfaction levels among educators and students, reflecting a more interesting and satisfying learning environment.